Relation between the system of public procurement and economic attractiveness: a comparative study of Latvia and Kenya - Svilāns, Pauls (Riga Graduate School of Law, 2023)
The problem of research considers how the working and organization of the public procurement systems in Latvia and Kenya, properly addresses their respective economic peculiarities and structural types of organization in way for a well-developed and favourable economic environment. For the resolution of the aim and problem of research, the Author proposes a division in objectives, covering the exploration of the economic environment in Latvia and Kenya, defining barriers to economic growth and prospective opportunities. Following, the Author will turn to the analyses of the standing regulatory environment of public procurements in the respective systems, where not only the current material framework shall be considered, but the inherent structure of institutional organization. Lastly, the Author shall turn back to the proposed problem of research, where it must be considered, how the developments and factual situation of public procurement address the apparent limitations in the advancement of the economic environment and competition in Latvia and Kenya, necessitate the future steps for a positively influential structure of procurement management. The result of the study proposes a rather differing outlook, where the correlation of an efficient working of the economic environment and procurement regulation is present, the effect of the rules on the market advancement, depends strongly on not only the strictly apparent system of regulation but more the factual organization and relation of parties.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law; Research Subject Categories::LAW/JURISPRUDENCE::Procedural law::Administrative procedure; Public procurement; Latvia; Kenya